Ny politikk på diabetesfeltet? Nøkkelinformanters syn på dagens og morgendagens tilbud - Foss, Christina; Knutsen, Ingrid Ruud (Nordisk tidsskrift for helseforskning, 2016)
New policy in type 2 diabetes care? Key informants’ assessment of today’s and tomorrow’s policyHealth care service for patients with chronic diseases has undergone fundamental changes in recent years: focus on self-management, de-centralisation to municipals with an emphasis on prevention and an urge for interdisciplinary and intersectoral collaboration. In the operationalization of the political signals to specific measures in the field, key actors’ understanding influences the formulation of policy. As part of a larger international study (EU-Wise) qualitative semi-structural interview was performed with 15 informants who hold key positions with an ability to influence the specific implementation of health policy for people with type 2 diabetes. The key informants showed abundant variation in what they saw as important challenges and measures. The informants have few descriptions of initiatives to fight social inequalities and were vague in their descriptions of measures that are not individual-oriented. The vagueness may indicate the need for more specific recommendations of measures in the field
Keywords: health policy; municipal care; chronic disease; keynote informants; Helsepolitikk; kommunehelsetjeneste; kronisk sykdom; nøkkelinformanter